Menggagas Constitutional Complaint Dalam Memproteksi Hak Konstitusional Masyarakat Mengenai Kehidupan dan Kebebasan Beragama Di Indonesia - Krisdanar, Vino Devanta Anjas (Jurnal Konstitusi, 2010)
Social needed of Indonesia people about Constitutional Complaint is urgent and must be held as an effort to protect constitutional rights of Indonesian people itself. The application of a concept without adaptation of new system to original system will make disorder the original system that has been used in Indonesia Law System. No many changes in adaptation of Constitutional Complaint to law system of Indonesia. The effort to protect constitutional rights of Indonesian people in life and freedom of religion must be selected carefully. Government has a duty to protect the society form deviate conviction that indicated can destroy the peace of society or hurt the other religion. For that case, Constitutional Complaint can’t be used as a mechanism to protect the deviate conviction for the reason to protect the life and freedom of religion. The mechanism of Constitutional Complaint as an authority of Constitutional Court first must held the socialization to all Indonesian people in order to the closeness between Indonesia people and Constitution of   Indonesia.